Blockchain as a Tool for the Formation of the Modern Creative Economy Industry: Processes, Strategies and Prospects of Application - Nataliia Mohylevska; Lesia Malooka; Kateryna Darovanets; Oleksandr Darovanets (Socio-Cultural Management Journal)
Introduction. The relevance of the research topic is due to the problems caused by the globalisation of society. The modern creative industry is going through a new digitalisation stage, transforming its content, organisational and stylistic components. Purpose and methods. The purpose of the article is to analyse the problems and prospects of using blockchain technology in the creative industry of Ukraine. The methodological basis of the study is a systemic-functional, dynamic, comprehensive principle that includes methods of analysis and synthesis, modelling, historical and logical methods, and statistical analysis. Results. The article reveals the specifics of managing socio-cultural projects using blockchain and identifies the positive and negative results of its application. The scientific novelty of the research results is to reveal the socio-cultural essence of managing socio-cultural projects by using blockchain, identifying its positive features, negative consequences and threats to the artist and the user. Conclusions. The author analyses the legislative framework for the use of digital tools in the creative industry, in particular, the Law of Ukraine ‘On Culture’, the Law of Ukraine ‘On Virtual Assets’, the Law of Ukraine ‘On Amendments to the Tax Code of Ukraine and Other Legislative Acts of Ukraine Regarding the Regulation of the Turnover of Virtual Assets in Ukraine’, and assesses the legal regulation of blockchain technologies in the field of socio-cultural activities. The author assesses the level of blockchain development in the creative industry of Ukraine in the context of the war, and considers financial aspects, including the urgent need for investment and state support for blockchain-related projects.